Self-Regulated Learning in Accounting: Diagnosis, Dimensions and Explanations - Raimundo Nonato Lima Filho; Gerlando Augusto Sampaio Franco de Lima; Adriano Leal Bruni (BBR: Brazilian Business Review)
This research analyzes self-regulated learning in A ccounting students in two public universities, presenting diagnosis, dimensions and possible explanations, contextualized from the gender, age and stage in the course. The object ives of this paper include to: (a) identify the self-regulated learning strategies used by Accounti ng students in two public universities, (b) determine the dimensions associated with those stra tegies, and (c) analyze how these strategies could be explained on the basis of gende r, age or stage (semester) of the students in the course. A sample consisting of 249 individuals revealed that gender and age are factors that influence the degree of self-regulation of a s tudent. Women and younger students tend to have higher levels of self-regulated learning, howe ver, in the stage analysis, the results did not show normal distribution, thus demonstrating the im possibility of realizing the increase or decrease of the degree of self-regulated learning a mong respondents. These results contribute to the practice of teaching accounting, as older st udents and those with a male gender should receive more special attention in relation to their development of self-regulated, independent and proactive learning.